De Novo Design of Antimicrobial Peptides With a Special Charge Pattern and Their Application in Combating Plant Pathogens - Chen, Eric H. -L.; Weng, Cheng-Wei; Li, Yi-Min; Wu, Ming-Chin; Yang, Chien-Chih; Lee, Kung-Ta; Chen, Rita P. -Y.; Cheng, Chiu-Ping (Frontiers in Plant Science, 2021)
Plant diseases are important issues in agriculture, and the development of effective and environment-friendly means of disease control is crucial and highly desired. Antimicrobial peptides (AMPs) are known as potential alternatives to chemical pesticides because of their potent broad-spectrum antimicrobial activity and because they have no risk, or have only a low risk, of developing chemical-resistant pathogens. In this study, we designed a series of amphipathic helical peptides with different spatial distributions of positive charges and found that the peptides that had a special sequence pattern “BBHBBHHBBH” (“B” for basic residue and “H” for hydrophobic residue) displayed excellent bactericidal and fungicidal activities in a wide range of economically important plant pathogens. The peptides with higher helical propensity had lower antimicrobial activity. When we modified the peptides with a long acyl chain at their N-terminus, their plant protection effect improved. Our application of the fatty acyl-modified peptides on the leaves of tomato and Arabidopsis plants lessened the infection caused by Pectobacterium carotovorum subsp. carotovorum and Botrytis cinerea. Our study provides important insights on the development of more potent novel AMPs for plant protection.